Frederick - Lionni, Leo, 1910-1999. (New York : Knopf : Distributed by Random House, 1987)
Frederick, the poet mouse, stores up something special for the long cold winter.
"Dragonfly Books."
Caldecott Medal/Honor
Elem. School Library Collection
Wilson's Children
Booklist, April 2004
Child Study Children's Book Committee, April 2004
Keywords: Mice -- Fiction; Mice -- Fiction